2015
DOI: 10.1186/s40064-015-1400-1
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell transplantation therapy in Parkinson’s disease

Abstract: Ineffective therapeutic treatments and inadequate repair ability in the central nervous system are disturbing problems for several neurological diseases. Fortunately, the development of clinically applicable populations of stem cells has provided an avenue to overcome the failure of endogenous repair systems and substitute new cells into the damaged brain. However, there are still several existing obstacles to translating into clinical application. Here we review the stem-cell based therapies for Parkinson’s d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 105 publications
1
31
0
Order By: Relevance
“…Therefore, new strategies based on the use of stem cells, such as neural stem cells (NSCs), have emerged as an alternative therapy for PD . NSCs are multipotent stem cells isolated from fetal and adult nervous system tissues with the ability to self‐renew and differentiate into specialized functional neurons and glial cells, making them an interesting source of cells for neuronal repair after injury or disease . In fact, different reports have already shown that the transplantation of NSCs display therapeutic effects, such as the capacity to protect and regenerate damaged DA neurons, as well as the potential to improve function in animal models of PD.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, new strategies based on the use of stem cells, such as neural stem cells (NSCs), have emerged as an alternative therapy for PD . NSCs are multipotent stem cells isolated from fetal and adult nervous system tissues with the ability to self‐renew and differentiate into specialized functional neurons and glial cells, making them an interesting source of cells for neuronal repair after injury or disease . In fact, different reports have already shown that the transplantation of NSCs display therapeutic effects, such as the capacity to protect and regenerate damaged DA neurons, as well as the potential to improve function in animal models of PD.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, these cells have been recognized for their ability to migrate to the wound area in order to integrate as neuroglia into preexisting circuits, ultimately helping to repair cellular damage. These findings have been clinically correlated with an improvement in both motor and cognitive performances in rodent and primate models of neurodegenerative syndromes such as Alzheimer's and Parkinson's disease (Berrío Sánchez, Cucarián Hurtado, & de Oliveira, ; Fu et al, ; Kikuchi et al, ; McGinley et al, 2018; Moon et al, ; Yang, Zhang, Oldenburg, Ayala, & Zhang, ). Similar advantageous effects have been reported in certain clinical trials including patients with either traumatic central nervous system injuries, neurodegenerative pathologies, or peripheral nerve damage, with these effects apparently more pronounced in terms of restoration of locomotor function compared to cognitive performance (Song et al, ; Volkman & Offen, ).…”
Section: Introductionmentioning
confidence: 92%
“…Cell‐based therapies have been proposed as promising therapeutic approaches, both to functional recovery in damaged nervous tissue and to restrain the progress of endorse PD (Fu et al, ). Approximately 30 years ago, stem cells were being collected from bone marrow and used for the pioneering treatment of bone marrow transplantation to treat blood diseases (de la Morena & Gatti, ).…”
Section: Introductionmentioning
confidence: 99%
“…Rigidity, resting tremor and bradykinesia are the major symptoms which make PD the most common movement disorder of the world affecting individuals post 65 years of age (Fu et al, 2015). Mechanistic and pathophysiological studies have given us a deep understanding of the disease.…”
Section: Parkinson's Disease (Pd)mentioning
confidence: 99%